Figured dark : poems - Rappleye, Greg (Book collections on Project MUSE., 2007)
Greg Rappleye is corporation counsel for Ottawa County, Grand Haven, Michigan. He's the author of two poetry collections, Holding Down the Earth and A Path Between Houses, and two chapbooks. A past Bread Loaf Fellow in poetry, he has won a number of awards, including a Pushcart Prize, the Paumanok Poetry Award, and the Brittingham Prize, and he was the first runner up for the 2007 Dorset Prize.